A theoretical approach to the waves of feminism: the fourth wave - Aguilar Barriga, Nani (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2020)
Abstract. This study aims to give visibility to early feminist voices at first, individually through their works and in a second moment, collectively with the rise of the feminist movement, fought and are fighting for a society where man and woman are in a state of equilibrium; the same valuation and consideration and which have the same rights and opportunities. Thus, this analysis will delve into what are known as waves of feminism, which will emerge, how women from a situation of discrimination and invisibility, maintained and perpetuated throughout history by gender roles and patriarchy in all spheres of society; social, political, economic, completed focusing especially in the many mass demonstrations of women and feminist men in all parts of the world and, indicators that make it possible to speak of the existence of the Fourth Wave feminism and its objectives: The struggle for elimination of all forms of violence against women simply because they are women, including sexual violence and prostitution and parity between men and women in all areas.